Studi Pematahan Dormansi dalam Meningkatkan Daya Kecambah Benih Padi (Oryza sativa L.) Varietas Mekongga dengan Perlakuan GA3 - Fatmariani Abdul Wahab; Novri Youla Kandowangko; Jusna Ahmad (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Seed dormancy is one of the main factors that inhibit the process of germination and plant growth. This study aims to study the effectiveness of using gibberellic acid (GA3) in maintaining the dormancy of rice seeds (Oryza sativa L.) Mekongga variety to increase germination. In this study, Mekongga rice seeds that experienced dormancy were given GA3 treatment with various concentrations. 0.25 ppm, 0.50 ppm, and 0.75 ppm with 24- and 48-hour immersion. The parameters measured include germination percentage, maximum growing potential, dormancy intensity, and sprout length. This research uses a quantitative approach with experimental methods. This study was carried out using a factorial pattern Group Randomized Design (RAK), which consisted of two factors, namely four levels of soaking using three differences in GA3 concentration and one control (aquades) and two levels of seed immersion, namely 24 and 48 hours. The results showed that GA3 treatment in combination concentration treatment had an influence on observation parameters, and there was the best concentration, namely a concentration of 0.25 ppm in 48-hour soaking capable of producing the highest germination of 96.25%, maximum growth potential reaching 98.5% with a dormancy intensity value of 1.5%.